Rekonstruksi Jaringan Lunak Periodontal dengan Pembatasan Gerak Jaringan Smile Elevator untuk Koreksi Gummy Smile: Laporan Kasus - aulia adia; Shalahuddin Maulidi; Agung Krismariono (YARSI Dental Journal, 2026)
Introduction : In the modern era, dental esthetics has become an important consideration, particularly in cases of gummy smile, which may significantly reduce a patient’s self-confidence. A gummy smile is defined as excessive gingival display of more than 3 mm in the vertical dimension of the maxillary anterior region during smiling. The etiology of gummy smile is multifactorial and may include hyperactivity of the upper lip elevator muscles, vertical maxillary excess, and delayed passive eruption. Case Report: A 32-year-old woman presented with the chief complaint of excessive gingival display during smiling and dissatisfaction with poorly fabricated veneers, which negatively affected her confidence. She also reported halitosis following veneer placement performed at a non-clinical setting. Intraoral examination of the maxillary and mandibular anterior regions revealed poor-quality veneers, hyperemic and edematous gingival margins, and abnormal gingival texture. Discussion: A pleasant smile requires harmony among tooth shape, color, size, gingival health, and an appropriate amount of gingival display during smiling. This case report describes a surgical approach combining periodontal soft tissue reconstruction with smile elevator tissue containment for the correction of gummy smile. The technique aims to reduce excessive gingival display by limiting the excessive retraction of the smile elevator muscles. Conclusion: Periodontal soft tissue reconstruction in combination with smile elevator tissue containment represents an innovative surgical technique for the correction of gummy smile.